A perfect 'treatment-society'? - Niels Rosendal Jensen (Social Work & Society, 2004)
The Danish Minister of Social Affairs is a very eager protagonist of quality in treatment, almost searching for the "perfect" treatment for children, youngsters, disabled, etc. Many expensive research projects dealing with quality management as well as developmental projects have been launched during the latest years in order to improve professional practice. Within that context this article will deal with the relations between paternalism and ignorance and between pro-social behaviour and anti-social treatment in order to grasp "why professions are doing vicious things". The main focus is concerned with the knowledge field of social pedagogy.